Modelling Peak Ground Acceleration (PGA) Using Tweedie Generalized Linear Model: Case Study Padang's Earthquake in 2009 - SAFIQ UBAY (NIM : 20813004); Pembimbing : Dumaria R. Tampubolon, Ph.D, MUHAMMAD
Large magnitudes of earthquakes may cause loss of lives and/or great financial losses due to damages on properties/infrastructures and business interruptions. To reduce the risk of damages on properties in a particular location, the potential damages need to be predicted by calculating the ground motion. The Peak Ground Acceleration (PGA) as a parameter of ground motion in a particular location is a function of the moment magnitude of the earthquake, the distance of the location from the epicenter, and the type of soil at the location. In this thesis, the equation of the PGA is modeled using generalized linear model (GLM). The PGA data analyzed in this thesis is that in the Megathrust Mid 2 Sumatera region caused by the Padang (Pariaman) earthquake on 30 September 2009